Efeitos da exposição ao mercúrio na fase pré-hipertensiva sobre a reatividade pressórica de ratos espontaneamente hipertensos - Ronchetti, Graziele Zandominegue (2019)
Mercury (Hg) is a toxic pollutant metal for the body. Studies show that exposure to Hg produces important deleterious effects on the cardiovascular system, such as endothelial dysfunction, increased production of reactive oxygen species, among others. Consequently it can also cause clinical complications, such as high blood pressure. The present study aimed to investigate the effects of mercury exposure in the prehypertensive phase on the pressure reactivity of spontaneously hypertensive rats. Male Wistar and SHR at 4 weeks were randomly divided into 4 groups: Wistar not exposed to Hg (Wistar Ct), Wistar exposed to Hg (Wistar Hg); SHR not exposed to metal (SHR Ct) and SHR exposed to Hg (SHR Hg) for 30 days. Before and during exposure, animals from the 4 groups were submitted to blood pressure measurement by tail plethysmography. At the end of exposure, the animals underwent right jugular vein and right carotid artery catheterization surgery for the administration of drugs: L NAME, TEMPOL and LOSARTAN, as well as hemodynamic parameters measurement: systolic (SBP) and diastolic blood pressure ( DBP), which occurred after normalization of the initial registration and normalization after 30 minutes of drug administration. By the α1 adrenergic agonist phenylephrine, two reactivity curves were performed, also before and after the drugs. Plasma nitrite and nitrate, Angiotensin converting enzyme (ACE) activity in the heart, and TBARS (thiobarbituric acid reactive substances) in the aorta were also evaluated. In SHR Ct, the increase in SBP by indirect measure was evidenced from the second week. However, in HRS exposed to Hg, this increase was accelerated and sustained until the end of the exposure period, when SBP was 132 ± 1.5 mmHg and 135 ± 3.0 mmHg 143 ± 2.3 mmHg and 166 ± 3.5 mmHg, respectively for the Wistar Ct and Hg group and SHR Ct and Hg, suggesting that the metal may be involved in SBP increase in the SHR Hg group. Administration of L-NAME in the direct pressure measurement increased SBP and DBP in all study groups, but the increase was lower in Hg-exposed SHR, suggesting that metal exposure is related to decreased NO bioavailability. . The decrease of nitrite and nitrate in the SHR Hg group (25% compared to SHR Ct) also suggested that mercury reduces NO bioavailability in this group, however no changes were observed in Wistar animals exposed or not to the metal. After administration of TEMPOL, decreased SHR Hg SBP and increased lipid peroxidation were observed. Regarding LOSARTAN, not after 20 administration of LOSARTAN, there was a decrease in SBP and DBP in all groups, with lower SBP magnitude of animals exposed to Hg. It was also possible to notice a decrease in ACE activity in the SHR Hg group, suggesting that the metal decreases the enzyme activity, or culminates in the lower return of angiotensin I to angiotensin II, which in turn directly interferes with AT1 receptor response. . Regarding pressure reactivity, Hg did not interfere with the phenylephrine response in groups, but when L NAME was administered, it removed an increase in reactivity response only in the SHR Ct group in SBP, suggesting what Hg may lose a. bioavailability of NO in young SHR. EROS mediation was evaluated again with the administration of TEMPOL, which was not able to interfere with group reactivity, nor with the administration of LOSARTAN, there was no interference with reactivity response in either group. The results show that the effects of mercury exposure recorded in the studied analyzes may trigger acceleration or development of hypertension, related mainly to a decrease in NO bioavailability and increased oxidative stress.